Robert Duncan and the Vernacular of Preliteracy - J. Peter Moore (Sillages Critiques)
In 1947, Robert Duncan wrote to William Carlos Williams with great eagerness, enthusing about his desire, aided by his reading of Williams’s poetry, to “bring into active concern this whole question of the new vernacular.” This paper asks what Duncan means by a “new vernacular.” In contrast to naturalistic representations, which establish the vernacular as an organic reflection of national character, recognizable through its distinctive lexicon and its antagonism towards sophistication, Duncan associates the category with an abstracted quality of expression that all speech holds in common. He imagines the vernacular not as a type of language, self-evident and easily recognized, but rather as an epistemological stage, previous to subject formation and language acquisition, and rooted in Dante Alighieri’s image of the child first acquiring speech from his nurses. Duncan recapitulates medieval cultural divisions between the father tongue of Latin grammar and the mother tongue of fluid speech and posits the vernacular as a counter-national field of pre-semantic sound, conveyed through feminine modes of relation. The poet’s task, in Duncan’s imagination, is to return to those seedbanks of language, to re-plant the words of that early stage, in order to activate an organic music arising from preliterate babble that might transcend the boundaries that segregate speech communities.